Self-determination theory : study of social factors that affect determination among secondary students to learn music in school / Erwina Lenny Niusan - Niusan, Erwina Lenny (2014)
The purpose of this thesis is to study the social factors that affect students’ self determination towards music learning in secondary school. This study applies the quantitative method to determine the degree of psychological needs and social factors affecting self—determination among secondary school to learn music in school. Data was collected using an online questionnaire that was answered by 36 secondary students from three schools in Klang Valley, Peninsular Malaysia‘ The findings fall into two categories: the degree of psychological needs that students receive and what social factors affect students” determination in learning music. Statistical analysis reveals that the overall impact on students’ self-determination in sustaining their music learning that is affected by parents, teacher and peers leads to both positive and negative effect on students’ music learning in school. The results contribute to 1.116 growing literature regarding self determination theory and social affect on music learning.